Strategi Orang Tua Dalam Mengatasi Kebiasaan Temper Tantrum Pada Anak Usia Dini di Kecamatan Langsa Baro - Zainuddin Zainuddin; Mulyadi Mulyadi; Muhibuddin Muhibuddin; Mohd. Nasir; Susilawati Susilawati (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The habit of temper tantrums carried out by children aged 2 to 6 years is an attitude that must be controlled well by parents, so that children can grow and develop emotionally well. Certain strategies are needed to overcome the child's temper tantrum habits. The purpose of this study was to determine the form of parenting style in dealing with temper tantrum behavior in early childhood and to determine the supporting and inhibiting factors of parenting parents in overcoming temper tantrum behavior in early childhood in Kecamatan Langsa Baro. This research uses a qualitative approach. The subjects (respondents) of the study consisted of three villages in Kecamatan Langsa Baroe, namely Geudubang Jawa, Geudubang Aceh and Paya Bujok Tunong. The research subjects are children with temper tantrum behavior, parents and community experts (psychologists). Data collection techniques using observation, interviews and documentation. While the data analysis technique is used to interpret the results of the study which consists of: data reduction, data presentation, and inference. The results of this study indicate that: 1) The form of parenting style in dealing with temper tantrum behavior in early childhood in Langsa BarÔ District is the tendency of parenting parents to overcome temper tantrum behavior such as authoritarian, permissive, and democratic. The supporting factors for parenting parents in overcoming temper tantrum behavior in early childhood in Langsa BarÔ District are: a) Parents' self-efficacy. b) Parents' social support. c) The role of the community of experts (psychologists). While the inhibiting factors include: a) Parents' mistakes because they always comply with the wishes of the child, b) Parents are too authoritarian towards children, c) The inability of children to express their expressions, d) Busy parents so that they pay less attention to children. The conclusion is that there are three strategies used by parents in dealing with children who have a temper tantrum, namely, first, using an authoritarian strategy where the child is forced to follow the wishes of the parents, Second, a permissive strategy, namely the child is given freedom to carry out his wishes, although sometimes the parents also help the child to fulfill their desires, and thirdly, a democratic strategy, where parents give children the freedom to fulfill their desires but under the control of the parents.